Backup Routing Algorithm Based on Delay Constraint in Cognitive Radio Sensor Networks. (19th October 2015) - Wu, Zhenguo; Liu, Xiaozhu; Zhang, Yan; Samani, Hooman; Zhu, Rongbo
In cognitive radio sensor networks (CRSNs), the frequency used by second users will be terminated unexpectedly as the preemption of primary user or reinitialized route discovery process in data transmission process, which will lead to unreliable communication and degrade the network performance greatly. In this paper, an efficient backup routing algorithm is proposed for reliable routing based on the uncorrelated degree and delay constraint in CRSNs. Numerical and simulation results show that the proposed algorithm can effectively overcome the intermittent connection problem and decrease delay greatly.